2021
DOI: 10.3906/sag-2010-336
|View full text |Cite
|
Sign up to set email alerts
|

The role of circadian rhythm in the regulation of cellular protein profiles in the brain

Abstract: Background/aim: Circadian rhythm plays a significant role in the regulation of almost all kinds of physiological processes. Besides this it may also have a direct or indirect effect on the neurodegenerative processes, including Alzheimer's disease, Parkinson's disease, and ischemic stroke. Therefore, the identification of circadian rhythm related proteins is crucial to be able to understand the molecular mechanism of the circadian rhythm and to define new therapeutic target for the treatment of degenerative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The levels of Pde10a transcript and protein display daily rhythms, which could be seen in preparations of the whole retina. Other studies have revealed the role of Pde10a gene in the circadian regulation [ 46 , 47 ]. The network graph constructed from the dynamic partial correlation is presented in the Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of Pde10a transcript and protein display daily rhythms, which could be seen in preparations of the whole retina. Other studies have revealed the role of Pde10a gene in the circadian regulation [ 46 , 47 ]. The network graph constructed from the dynamic partial correlation is presented in the Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gng7 is the abnormal protein of dopaminergic signaling 56 . CPne5 is the circadian rhythm-related proteins, and circadian rhythm have a direct or indirect effect on the neurodegenerative processes 57 , and more importantly, the gene is involved in PD-induced toxins like paraquat 58 . In accordance with the expression characteristics of these genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PSMB6, also known as 20S proteasome subunit beta-1, codes for the β1 core catalytic subunit of the proteasome (Vriend and Marzban, 2017). A study showed that PSMB6 was a critical regulator of circadian rhythm, which may also have a direct or indirect effect on neurodegenerative diseases (Beker and KiliÇ, 2020). Mitochondrial ribosomal protein large 17 (MRPL17) and Mitochondrial ribosomal protein large 24 (MRPL24) are one of the 82 protein components of mitochondrial ribosomes, playing an essential role in the mitochondrial translation process, but their relationship with neurodegenerative diseases is currently unclear (Nottia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%